A study of Islamic website design features - Mahmud, Murni (s.n, 2012)
This research aims to identify the Islamic website definition and build framework to define Islamic website’s content and design features. A lack of studies has been conducted to identify the weaknesses of current Islamic websites in order to gain trust of people who are interested to learn about Islam and/or to practice Islamic knowledge.